2022
DOI: 10.52131/jee.2022.0302.0029
|View full text |Cite
|
Sign up to set email alerts
|

Urban Population Growth, Per Capita Energy Use, and CO2 Emissions: Evidence from the World's fifth-most Populous Country

Abstract: Pakistan is the world’s 5th most populated country. This growing population is causing numerous social and environmental problems. By the increase in population, energy demand is increasing day by day. Pakistan, where majority of the population is living in rural areas is using uncleaned cooking fuel due to which CO2 emission is increasing that is further a cause of environmental degradation. Based on the data (for the period from 1980 to 2019) of World Development Indicators, this study intends to examine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Some researchers studied environmental degradation, especially CO2 emissions cause of various diseases in Pakistan such as skin allergy, cardiovascular disease, and asthma (Anwar, Ahmed, & Asghar, 2012;Majid, Madl, & Alam, 2012;Shahid & Hussain, 2013;Wang, Gillani, Nazir, & Razzaq, 2023). CO2 emissions is increased in the air because of the use of fossil fuels and this also causes climate change (Ahmad, Bhatti, Urooj, & Javed, 2022). CO2 emissions creates negative externalities and effects on both human health and economic growth.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers studied environmental degradation, especially CO2 emissions cause of various diseases in Pakistan such as skin allergy, cardiovascular disease, and asthma (Anwar, Ahmed, & Asghar, 2012;Majid, Madl, & Alam, 2012;Shahid & Hussain, 2013;Wang, Gillani, Nazir, & Razzaq, 2023). CO2 emissions is increased in the air because of the use of fossil fuels and this also causes climate change (Ahmad, Bhatti, Urooj, & Javed, 2022). CO2 emissions creates negative externalities and effects on both human health and economic growth.…”
Section: Introductionmentioning
confidence: 99%
“…The result showed that in Australia, economic growth is directly related to CO2 emission, while Trade and Renewable Energy have a negative relation with CO2 emission. Conversely, In Canada, CO2 emissions increase due to Economic growth, Trade and Urban population (Ahmad, Bhatti, Urooj, & Javed, 2022;Bhatti & Fazal, 2021). Adebayo, Awosusi, and Adeshola (2020) investigate the interlinkage between Energy usage, Trade, Urbanization, and Economic growth on CO2 emission using the ARDL PMG technique to analysis the panel data collecting from countries of MINT (Mexico, Indonesia, Nigeria and Turkey) varies from 1980-2018.…”
mentioning
confidence: 99%